Penerapan Akuntansi Manajemen Lingkungan Pada Rumah Makan Studi Kasus di Kota Gorontalo - Mattoasi Mattoasi; Tri Herlina Nani; Dharmawaty S.Makur (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2021)
The existence of environmental management accounting in the organization aims to provide information on financial and non-financial aspects of the company's environmental performance. This study aims to determine the understanding of restaurant actors who have the mandatory status of implementing Environmental Management Efforts and Environmental Monitoring Efforts) on a regular basis. The research method used is a qualitative method (post positivism) which is expected to be able to express answers to a field phenomenon inductively. Data were collected based on triangulation with data analysis using the concept of Miles and Huberman (1994). The results of this study indicate that restaurant business actors' understanding of environmental management accounting information has an impact on financial reporting, especially environmental costs.